PHYSICAL, MECHANICAL, AND DURABILITY PROPERTIES OF INCORPORATION OF GRAPHENE OXIDE IN GEOPOLYMER MORTAR - Shamsol, A. S.; Apandi, N. M.; Zailani, W. W. A.; Rashid, A. S. A. (Journal of Engineering and Technology (JET), 2026)
This study examines the impact of integrating nano powder graphene oxide (GO) into ground granulated blast slag (GGBS) and fly ash class F (FA)-based geopolymer mortar (GPM). The study assesses the flowability, compressive strength, and chloride ion permeability of GPM with different GO dosages (0.02 wt.%, 0.04 wt.%, 0.06 wt.%, 0.08 wt.% and 0.10 wt.%). The findings demonstrate that the incorporation of 0.04 wt.% GO increases the compressive strength by 61.21% (early strength) and 50.75% (late strength) compared to the control specimen. Additionally, chloride ion permeability reduced by 35.3%, with elevated GO dosages. The Rapid Chloride Permeability Test (RCPT) was performed to evaluate the chloride ion resistance of geopolymer concrete enhanced with graphene oxide. The addition of graphene oxide (GO) up to 0.06% frequently decreases chloride ion permeability. The smallest results were observed at a GO content of 0.06% for both mixes with a water-to-precursor ratio (w/p) of 0.1 and 0.2. The experimental results demonstrated that the geopolymerization products exhibited remarkable compactness, and the internal porosity diminished due to the inclusion of GO. The results indicate that the integration of GO into GGBS-FA-based GPM markedly enhances its physical, mechanical and durability properties, supporting its wider utilisation in sustainable building.